1988
DOI: 10.1111/j.1460-2466.1988.tb02051.x
|View full text |Cite
|
Sign up to set email alerts
|

The British, Canadian, and U.S. Pornography Commissions and Their Use of Social Science Research

Abstract: A reyfew of the tbree commissions in terms of tbeir &?itions ofpomgraplry, tbeirpos2tions on ttspotenEiclr eflkcts, and tbeir r e c -' sbows&studal uar&z&m in sociopolitical i-Wm and regard for socidscienceeuidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Pornography debates in the 1980s. As the experimental link between pornography and aggression strengthened in the early 1980s (Donnerstein & Berkowitz, 1981;Linz, Donnerstein, & Penrod, 1984;Zillmann & Bryant, 1982), three government committees were convened (the Williams Committee in the United Kingdom in 1979, and the Fraser Committee in Canada and the Attorney General's Commission on Pornography in the United States, both in 1986) that took this research into account (Einsiedel, 1988). These committees drew sharp criticism from scholars concerned with civil liberties (Brannigan, 1991;Fisher & Barak, 1991;Segal, 1990), and some aggression researchers themselves spoke out, appalled at the thought of their own data giving license to government censorship (Linz, Penrod, & Donnerstein, 1987;Wilcox, 1987).…”
Section: Social and Political Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Pornography debates in the 1980s. As the experimental link between pornography and aggression strengthened in the early 1980s (Donnerstein & Berkowitz, 1981;Linz, Donnerstein, & Penrod, 1984;Zillmann & Bryant, 1982), three government committees were convened (the Williams Committee in the United Kingdom in 1979, and the Fraser Committee in Canada and the Attorney General's Commission on Pornography in the United States, both in 1986) that took this research into account (Einsiedel, 1988). These committees drew sharp criticism from scholars concerned with civil liberties (Brannigan, 1991;Fisher & Barak, 1991;Segal, 1990), and some aggression researchers themselves spoke out, appalled at the thought of their own data giving license to government censorship (Linz, Penrod, & Donnerstein, 1987;Wilcox, 1987).…”
Section: Social and Political Contextmentioning
confidence: 99%
“…Much of the history—and much of the empirical research—that I review has taken place in the United States, where individuals typically are less accepting of alternative sexual practices relative to other Western societies (Hofstede, ). These cultural differences help provide context, for example, for studies in Australia (McKee, ) or the Netherlands (Hald & Malamuth, ) in which participants emphasized the positive aspects of pornography consumption, or for government commissions in the United States (e.g., Attorney General's Commission on Pornography, ) that have shown pornography in a particularly unfavorable light (Einsiedel, ).…”
Section: The Family Impact Lens and Important Limitationsmentioning
confidence: 99%
“…Based on divergent perspectives about the nature of the existing effects, the recommendations and conclusions of the reports differ. Judging from the literature after the publication and dissemination of the reports, little consensus was achieved (Einsiedel, 1988(Einsiedel, ,1989Koop, 1987;Lab, 1987;Mould, 1990;Nobile & Nadler, 1986;Pritchard, 1989).…”
Section: Controversy Over Conclusion From Current Researchmentioning
confidence: 99%
“…This was based on the categories of sexually explicit materials approach, with the Canadian court agreeing that sexually explicit materials with violent content and sexually explicit materials with non-violent but degrading and dehumanizing elements would be considered obscene and therefore legally actionable. The highest court of Canada thus essentially agreed with the United States commission's social science findings, disagreed with its own commission's internal research evaluation (which summarily dismissed most of the pornography research; see Einsiedel, 1988), and based its ruling on the notion that harmful sexually explicit material (i.e., the two classes mentioned above) "predisposed persons to act in an antisocial manner. "…”
Section: Conceptuauzing the Problemmentioning
confidence: 93%
“…A policy analyst similarly observed that the difference in recommendations was the result "not of different empirical findings, but of different judgments about similar findings" (Wilson, 1971, p. 47). Indeed, this differential judgment about the same issue has been documented in the case of three countries' varying responses to social science research on pornography (Einsiedel, 1988).…”
Section: The Lnterpretation Ofdatamentioning
confidence: 94%